2000
DOI: 10.4141/a99-118
|View full text |Cite
|
Sign up to set email alerts
|

In situ rumen degradation characteristics of sixty cultivars of barley grain

Abstract: In situ rumen degradation characteristics of sixty cultivars of barley grain. Can. J. Anim. Sci. 80: 691-701. Our objectives were to determine the extent of genetic variability in the rate and extent of ruminal digestion among 60 cultivars of barley, and to evaluate the correlations between ruminal digestion characteristics and chemical composition and test weight of barley cultivars. Barley samples were ground through a 2-mm screen, and bags containing 1 g of ground grains were incubated in the rumen of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…Differences in the nutritional characteristics within and among barley varieties have been reported (Molina-Cano et al, 1997;Khorasani et al, 2000). The range of values for the chemical composition in this study is similar to those reported earlier (Yang et al, 2000;Ramsey et al, 2001) and tabular values in NRC (2001).…”
Section: Chemical Compositionsupporting
confidence: 86%
“…Differences in the nutritional characteristics within and among barley varieties have been reported (Molina-Cano et al, 1997;Khorasani et al, 2000). The range of values for the chemical composition in this study is similar to those reported earlier (Yang et al, 2000;Ramsey et al, 2001) and tabular values in NRC (2001).…”
Section: Chemical Compositionsupporting
confidence: 86%
“…Processing improves digestibility of barley grain, and the effects of various processing methods on cattle performance have recently been reviewed (Dehghan-Banadaky et al 2008). Barley grain varies considerably in its physical characteristics; Khorasani et al (2000) reported that the weight of 1000 kernels ranged from 42.9 to 53.9 g among 60 cultivar lots. Kernel uniformity is influenced by barley variety as well as growing conditions.…”
mentioning
confidence: 99%
“…The first, in vivo, is characterised by feeding animals with known amounts of sample and measuring faecal output (Matsushima 1979). Although in vivo analysis is accurate and has been extensively used, it is expensive and requires a large amount of grain for the evaluation of a small number of samples (Khorasani et al 2000). The second method, an in vitro approach, determines digestibility by simulating ruminal chemistry and enzymatic reactions (McDonald et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The third method is an in situ technique, which involves the insertion of multiple non-digestible porous nylon bags, filled with grain samples, into the rumen of cannulated animals. This allows the amount of dry matter digested within the bag to be measured over a set period (Herrera-Saldana et al 1990;Khorasani et al 2000) and provides data from within the rumen itself. Ruminal digestion of incubated samples in the nylon bag can be affected by a number of factors, such as bag and sample size, bag material, pore size, sample processing, animal diet, feeding level and frequency, bag insertion and removal procedures, location of the bag in the rumen, rinsing procedure, microbial correction and incubation time.…”
Section: Introductionmentioning
confidence: 99%